PERSEPSI REMAJA PUTRI TENTANG VAKSINASI KANKER SERVIKS DENGAN MOTIVASI MELAKUKAN VAKSINASI HUMANPAPILLOMA VIRUS (HPV) - Dewa Ayu Surinati (Jurnal Gema Keperawatan, 2018)
Cervical cancer is the fourth most common cancer among women in the world. Based on this, primary prevention is increasingly encouraged by the government through HPV vaccination. However, the participation of women in HPV vaccination is still very low. The purpose of this study to determine the relationship of adolescent perceptions about cervical cancer vaccination with motivation to perform HPV vaccination. This research is correlational research with cross sectional approach. Sampling using proportional random sampling technique with a sample of 117 respondents. The results showed that most of the adolescent girls had good perception 53,8% and most of the girls had moderate motivation to do HPV vaccination that was 51,3%. The result of spearman statistic test obtained p-value = 0,000 alpha (0,05), hence can be concluded that there is relation of adolescent perception about cervical cancer vaccination with motivation to do HPV vaccination.